Estimations of the Financial Support Model for Tertiary Education in Lithuania - Čekanavičius, Linas; Grebliauskas, Artūras; Miliauskas, Giedrius (Ekonomika, 2008)
The present conditions of economic and social welfare and the pace of their development are highly influenced by the available “human capital”, especially its quality. Unfortunately, there is enough evidence that the competence of Lithuanian graduates is hardly sufficient to meet either present or future requirements of the labour market. The insufficient quality of university studies has opened a deep breach between the offers and the demands of labour market. The “accidental” choice of study programmes and low motivation of students combined with insufficient financial resources and rather poor facilities are important factors of such gap. The lack of competition between tertiary education institutions in terms of quality of the their students and graduates is another key factor of deficiency of the higher education system in Lithuania. This paper examines the Lithuanian system of tertiary education with the aim to reveal the roots of its deficiencies and offer a new financial model for tertiary education that may solve many of the existing problems. To achieve this goal, the main global trends in the development of higher education financial support models are reviewed, competition factors operating in tertiary education institutions are evaluated, sources and instruments for the financial support of tertiary education and scientific research are analysed in the paper. The suggested model is based on the assumption that the main responsibility of the state is to ensure accessibility of studies for capable individuals regardless of their social status. It is argued here that instead of state set study costs per student in various study programmes, the accessibility of studies must be controlled by the state-stipulated fixed minimum amount of financial support available to all students. Furthermore, it is argued that promoting competition among tertiary education institutions should be based upon available information in the higher education system, diminishing the risk of asymmetry of information. The proposed financial model shows that financial sources can be adequately and efficiently arranged to avoid any distortions in the motivation systems of the stake holders, i.e. students, state, educational institutions and employers.